2011 IEEE Symposium on Underwater Technology and Workshop on Scientific Use of Submarine Cables and Related Technologies 2011
DOI: 10.1109/ut.2011.5774157
|View full text |Cite
|
Sign up to set email alerts
|

NEMO-SN1 (Western Ionian Sea, off Eastern Sicily): Example of architecture of a cabled observatory

Abstract: NEMO-SN1, located in the central Mediterranean Sea, Western Ionian Sea, off Eastern Sicily Island (Southern Italy) at 2100 m water depth, 25 km from the harbour of the city of Catania, is a prototype of a cabled deep-sea multiparameter observatory and the first operating with real-time data transmission in Europe since 2005. NEMO-SN1 is also the first-established node of EMSO (European Multidisciplinary Seafloor Observatory, http://emso-eu.org), one of the incoming European large-scale research infrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Beranzoli et al, 2000;Favali et al, 2002;De Santis et al, 2006;Gasparoni et al, 2015) and ORION -Ocean Research by Integrated Observatory Networks-(e.g. Beranzoli et al, 2009;Favali et al, 2011) European Projects and the national project MABEL (e.g. Calcara et al, 2001).…”
Section: European Multidisciplinary Seafloor and Water Column Observa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Beranzoli et al, 2000;Favali et al, 2002;De Santis et al, 2006;Gasparoni et al, 2015) and ORION -Ocean Research by Integrated Observatory Networks-(e.g. Beranzoli et al, 2009;Favali et al, 2011) European Projects and the national project MABEL (e.g. Calcara et al, 2001).…”
Section: European Multidisciplinary Seafloor and Water Column Observa...mentioning
confidence: 99%
“…Important results have been obtained during the developments of these mentioned projects, such as the monitoring and study of the Marsili seamount (e.g. Favali et al, 2011;Italiano et al, 2014;Giovanetti et al, 2016), understanding the geolectrical conductivity under some exploring sites of Southern Tyrrhenian Sea (Di Vitale et al, 2009), designing an original tsunami early warning system (Chierici et al, 2012), showing the importance of a multiparameteric geophysical, environmental and oceanographic monitoring (e.g. Monna et al, 2014), to mention just some of the found results.…”
Section: European Multidisciplinary Seafloor and Water Column Observa...mentioning
confidence: 99%
See 1 more Smart Citation